STUDI KEANEKARAGAMAN MIKROALGA DI SUNGAI DAN DANAU BENGKULU SEBAGAI BIOINDIKATOR PERAIRAN - Oktaria Silviani; Bhakti Karyadi; Sipriyadi Sipriyadi; Dewi Jumiarni; Abdul Rahman Singkam (Jurnal Biosilampari : Jurnal Biologi, 2022)
This exploratory study aims to analyze the water quality of Selagan River and Tes Lake based on diversity of microalgae. Sampling was done by systematic purposive sampling. Results of study found 38 species (8 classes) of microalgae in Selagan River and 48 species (9 classes) in Tes Lake. The bundance of microalgae at the upstream, middle, and downstream stations of Selagan River were 3714 ind/ml, 105 ind/ml, and 315 ind/ml, with diversity index 0.25; 1.93; and 1.72. The microalgae dominance index in river is 0.95; 0.58; and 0.75 low to high criteria. The evenness index value for each station is 0.09; 0.78; and 0.63 low to high categories. Meanwhile, abundance of microalgae in Tes Lake at the inlet, middle, and outlet stations were 192 ind/ml, 204 ind/ml, and 200 ind/ml, with diversity index of 2.70; 2.55; and 2.05. The microalgae dominance index was 0.10; 0.28; and 0.2 low category. The evenness index value for each station is 0.78; 0.75; 0.64 high category. Conclusion, condition of Selagan River at the upstream station is classified as heavily polluted, the middle and downstream stations are classified as clean. Meanwhile, condition of Tes Lake is clean and shows normal tolerance range for microalgae life.